PENINGKATAN KEMAMPUAN PEMAHAMAN MATEMATIKA MELALUI PENDEKATAN PROBLEM POSING PADA SISWA KELAS X SMA NEGERI 19 MAKASSAR. - Bahar, Bahar (STKIP Pembangunan Indonesia Makassar, 2017)
This inquiry was classroom action research conducted at class X of SMA Negeri 19 Makassar. Which aimed at improving student mathematical comprension through problem posing approach. The research samples were 35 class X students of SMA Negeri 19 Makassar. Data collecting techniques used were observation, student response and essay test. The action was implemented within two cycles. Data were analyzed using both quantitative and qualitative analyses. After implementing problem posing approach, there results were as follows: (1) Within the first cycle, students’ ability of problem solving was categorized as high with the average score 60,23. The students’ mastery learning was 40.00%. Within the second cycle, the average score of students’ ability of mathematical comprehension improved to 74,77 which was categorized as high. The students’ mastery learning also improved into 91.43%. (2) Score of ability mean comprension mathematical from cycle I to cycle II mount 60,23 becoming mount 74,77 and mount the student amount mounting to learn from 14 people (40,00%) becoming 32 people (91,43%). Thereby ability of mathematical comprehension class X SMA country 19 Makassar told to mount. Keyword: the Mathematical Comprehension Ability, Problem Posing Approach